The InfluenceOf Social Media Influencer Trust “Dimas Ramadhan” On The Tourism Destination Decision-Making Process - Alamsah, Deden Burhanudin; Millanyani, Heppy (eProceedings of Management, 2025)
This study examines the influence of Dimas Ramadhan, a prominent Indonesian travel influencer, on the decision-making process of potential travellers. Social media has significantly impacted consumer behaviour, especially in the tourism sector, making it essential for businesses to understand influencer marketing. The research aims to analyze how Dimas Ramadhan’s credibility and trust affect his followers' choice of tourist destinations. Using a quantitative approach, data was collected from 250 respondents through a structured questionnaire. Structural Equation Modeling (SEM) with SmartPLS 4.0 was applied to analyze the causal relationship between influencer trust and decision-making. Findings reveal that Dimas Ramadhan’s credibility significantly influences his followers' travel decisions. Effective marketing communication through influencers enhances consumer engagement and increases purchasing behaviour. This study highlights the importance of collaboration between tourism businesses and credible influencers to improve marketing strategies. By emphasizing the role of trust in influencer marketing, this research provides valuable insights for tourism businesses. Future studies could explore the long-term impact of influencer marketing and the role of other social media platforms in shaping consumer behaviour.Keywords: Social Media Influencer, Tourism Decision-Making, Consumer Behavior.